The Spillover Consequences of an Enforcement-First U.S. Immigration Regime. (November 2014) - Aranda, Elizabeth; Menjívar, Cecilia; Donato, Katharine M.
In our introduction to this special issue, we describe how the immigration enforcement-first regime has consequences that extend beyond the supposed target population of undocumented immigrants and spill over to other groups, including legal permanent residents, U.S.-born Latinos/as, and other U.S.-born residents. The papers in this special issue address whether and how spillover effects exist and the form that they take. Often they include social, psychological, and in some cases, physical harm, and together they illustrate that directly or indirectly, U.S. policy's emphasis on interior and external border enforcement affects all of us.